Decoloniality in physiotherapy education, research and practice in South Africa - Saul Cobbing (AOSIS, 2021)
Background: Historically, the profession of physiotherapy in South Africa has closely aligned itself with our former colonial master, the United Kingdom. Whilst efforts have been made in recent years to transform our profession, numerous challenges remain. An improved understanding of the topic of decoloniality is a useful and necessary way of beginning to address these challenges. Objectives: The aim of this opinion piece is to encourage further dialogue amongst South African physiotherapists working in all sectors - a dialogue that must focus on genuinely transforming our profession to be better suited to serving the majority of South Africans. Method: Global and local literature related to decoloniality is summarised for readers, followed by a closer scrutiny of how this topic relates to some of the challenges faced by the profession of physiotherapy in South Africa. Results: The evidence presented demonstrates that whilst some efforts have been made to transform South African physiotherapy, significant work and dialogue is required to bring about a true transformation of the profession. Conclusion: An honest and transparent conversation about decoloniality and transformation can assist in realising the potential of our profession, thereby improving the health and well-being of all South Africans. Clinical implications: Real engagement with this topic can assist in transforming who enters our profession, what we teach, where and why we conduct research and how we can ensure that physiotherapy practice contributes to real social justice by benefitting the majority of our population.